Current status of polyherbal formulation derived from ethnobotanicals - Sonali Aswal; Vidya Chauhan (Archive of Biomedical Science and Engineering - Peertechz Publications, 2020)
Aim: Polyherbal formulations have been an area of interest for researchers. Ethnobotanicals are evaluated for their effectiveness against diseases as an alternative for synthetic drugs. The present review aimed to discuss the efficacy of the polyherbal formulation. Method: In the present study, all the relevant data collected from classical texts and research articles from various offline and online sources included Scopus, Web of Science, and PubMed, for the current status of the polyherbal formulation. The present review circumscribes the importance of polyherbal formulation.